La sinodalità come «stile di pensiero». La partecipazione di un Ateneo alla missione della Chiesa - Donatis, Angelo Card De (Alpha omega, 2021)
Synodality and knowledge are two terms between which it is important not to exclude a positive relationship. Pope Francis has brought out synodality not only as a form of governance, but as a style of being the Church. In this style, one stage imposes itself as fundamental, that of dialogue and of listening. The extension of synodality to the different aspects of the life of the Church suggests the possibility of assuming this same style as an orientation for our thinking. Today the forms of knowledge have been multiplied, also within the confines of a single discipline; from this there flows the need for dialogue between these aspects of knowledge in view of making possible an increase in the quality of relationships between persons and human groups. The dimension of the gratuity of knowledge and of the encounterbetween different kinds of knowledge, which is always an encounter between persons, gives witness to the divine love for creatures and to the welcoming of every sign of this love present in the world. To provide space for this gratuity is a choice which qualifies the mission of an academic institution, as well as of the mission of the Church.